Recent Radiation within Y‐chromosomal Haplogroup R‐M269 Resulted in High Y‐STR Haplotype Resemblance. (24th February 2014) - Larmuseau, Maarten H. D.; Vanderheyden, Nancy; Van Geystelen, Anneleen; van Oven, Mannis; de Knijff, Peter; Decorte, Ronny
Summary: Y‐chromosomal short tandem repeats (Y‐STRs) are often used in addition to Y‐chromosomal single‐nucleotide polymorphisms (Y‐SNP) to detect subtle patterns in a population genetic structure. There are, however, indications for Y‐STR haplotype resemblance across different subhaplogroups within haplogroup R1b1b2 (R‐M269) which may lead to erosion in the observation of the population genetic pattern. Hence the question arises whether Y‐STR haplotypes are still informative beyond high‐resolution Y‐SNP genotyping for population genetic studies. To address this question, we genotyped the Y chromosomes of more than 1000 males originating from the West‐European regions of Flanders (Belgium), North‐Brabant and Limburg (the Netherlands) at the highest resolution of the current Y‐SNP tree together with 38 commonly used Y‐STRs. We observed high resemblance of Y‐STR haplotypes between males belonging to different subhaplogroups of haplogroup R‐M269. Several subhaplogroups within R‐M269 could not be distinguished from each other based on differences in Y‐STR haplotype variation. The most likely hypothesis to explain this similarity of Y‐STR haplotypes within the population of R‐M269 members is a recent radiation where various subhaplogroups originated within a relatively short time period. We conclude that high‐resolution Y‐SNP typing rather than Y‐STR typing might be more useful to study population genetic patterns in (Western) Europe.